(untitled) (London, 2000)
This important treatise reviews the latest clinical models for working with developmental disability and behavioral problems. In the first section contributions explore the causes and nature of behavior problems among people with physical, learning, language, and sensory disabilities, and such specific conditions as epilepsy and acquired brain damage, while those in the second section describe the assessment approaches for evaluating these behaviors. The third section covers treatment strategies emphasizing the importance of an eclectic approach. The contributors, all acknowledged experts in their fields of pediatrics, psychology, and psychiatry, provide a comprehensive overview of this set of major challenges, indicating the importance of auditory detection, understanding, measurement, and treatment.
Keywords: Developmentally disabled children,Children with mental disabilities,Developmental disabilities,Developmental psychology,Dị tật bẩm sinh ở trẻ em,Tinh thần trẻ em khuyết tật,Phát triển khuyết tật,Phát triển tâm lý; Mental health,Psychology,Sức khoẻ tinh thần,Tâm lý